The French Revolution in theory - Wahnich, Sophie (Reinventing critical theory., 2022)
It is time to re-examine the French Revolution as a political resource. The historiography has so far ignored the question of popular sovereignty and emancipation; instead the Revolution has been vilified as a matrix of totalitarianisms by the liberals and as an ethnocentric phenomenon by postcolonial studies. This book examines why.